Global Financial Economy Crisis - Fluturim Saliu; Fatmir Memaj (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Global world economy crisis had its roots in the Covid 19 pandemic. The key factors back then were a combination of the macroeconomic processes and initialization in micro economic financial levels. Global trade began to recover from the negative impacts brought by the COVID- 19 pandemic in June 2020. As it was obvious for the world’s financial economic institutions, the expectations after the pandemics were to overcome the economic crises and start the growth of the world trade markets. Instead of that in 2022 the Russian aggression on Ukraine has made the financial crisis even worse and bended the world on the knees. The world now lacks on gas, oil, grain and the most important electrical energy. Both Russia and Ukraine were and still are the global source raw material markets, especially for energy, food and fertilizers, but since the war has no looks on ending, the severe restrictions that are up for the world’s population may bring the worst still not expected rise of the financial crisis